Viral hemorrhagic septicemia virus alters turbot Scophthalmus maximus macrophage nitric oxide production - Tafalla, Carolina; Figueras Huerta, Antonio; Novoa, Beatriz (Diseases of Aquatic Organisms, 2001)
7 pages, 4 figures. The effect of viral hemorrhagic septicemia virus (VHSV) in vitro infection on the nitric oxide (NO) production by turbot Scophthalmus maximus kidney macrophages has been addressed in the past. Previously, we had determined that only a small fraction of turbot possess head kidney macrophages that respond to a single exposure of lipopolysaccharide (LPS) with NO production (LPS-responsive macrophages), whereas macrophage cultures from other individuals were not activated by LPS alone and needed a combination of stimuli to respond (LPS-non-responsive macrophages). In the current work, we examined the effect of VHSV on NO production by macrophages characterized as LPS-responsive macrophages or LPS-non-responsive macrophages. Combinations of LPS and tumor necrosis factor α (TNF-α) and macrophage-activating factor (MAF) were also used to stimulate the cells for NO production. The effect of VHSV on NO production depends on the response to LPS alone. When a low multiplicity of infection was used (1.78 x 10-3), the NO production in response to LPS in LPS-responsive macrophages was significantly decreased. However, LPS-non-responsive macrophage cultures produced NO when a combination of LPS and VHSV was used. In the case of a higher VHSV multiplicity of infection (1.78), no significant change was observed in LPS-non-responsive animals. Combinations of LPS with TNF- α, LPS with MAF, and TNF-α with MAF were used to induce NO production in LPS-non-responsive macrophages. In all these cases, VHSV suppressed NO production, although at a significant level only when a combination of TNF-α and MAF was used for the induction of NO. This research was supported by grant MAR 96-1775 from the Comisión Interministerial de Ciencia y Tecnología (CICYT) (Spain). C.T. acknowledges the Fundación Ramón Areces for a research fellowship. Peer reviewed